The WHO’s 75th anniversary: WHO at a pivotal moment in history - Lawrence O Gostin; Roojin Habibi; Benjamin Mason Meier; Helen Clark; K Srinath Reddy; Jemilah Mahmood; Danwood Mzikenge Chirwa; Björn Kümmel; Winnie Mpanju-Shumbusho; Attiya Waris; Miriam K Were (BMJ Global Health)
The World Health Organisation (WHO) was inaugurated in 1948 to bring the world together to ensure the highest attainable standard of health for all. Establishing health governance under the United Nations (UN), WHO was seen as the preeminent leader in public health, promoting a healthier world following the destruction of World War II and ensuring global solidarity to prevent disease and promote health. Its constitutional function would be ‘to act as the directing and coordinating authority on international health work’. Yet today, as the world commemorates WHO’s 75th anniversary, it faces a historic global health crisis, with governments presenting challenges to its institutional legitimacy and authority amid the ongoing COVID-19 pandemic. WHO governance in the coming years will define the future of the Organisation and, crucially, the health and well-being of billions of people across the globe. At this pivotal moment, WHO must learn critical lessons from its past and make fundamental reforms to become the Organisation it was meant to be. We propose reforms in WHO financing, governance, norms, human rights and equity that will lay a foundation for the next generation of global governance for health.